2016
DOI: 10.1007/jhep06(2016)138
|View full text |Cite
|
Sign up to set email alerts
|

Phase space analysis of bulk viscous matter dominated universe

Abstract: Abstract:We consider a Friedmann model of the universe with bulk viscous matter and radiation as the cosmic components. We study the asymptotic properties in the equivalent phase space by considering the three cases for the bulk viscous coefficient as (i) ζ = ζ 0 , a constant (ii) ζ = ζ 0 + ζ 1ȧ a , depending on velocity of the expansion of the universe and (iii) ζ = ζ 0 + ζ 1ȧ a + ζ 2ä a , depending both on velocity and acceleration of the expansion of the universe. It is found that all the three cases predic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 82 publications
0
32
0
Order By: Relevance
“…The effect of bulk viscosity was primarily analysed in the context of acceleration in the early universe, the inflationary epoch [7]. In recent times, the effect of bulk viscous matter in causing the late acceleration was analysed by many [8][9][10][11][12][13][14]. In a recent review, Brevik et al [15] have shown important implications and capabili-ties of viscosity in describing inflationary era and late time acceleration of the universe; see also Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of bulk viscosity was primarily analysed in the context of acceleration in the early universe, the inflationary epoch [7]. In recent times, the effect of bulk viscous matter in causing the late acceleration was analysed by many [8][9][10][11][12][13][14]. In a recent review, Brevik et al [15] have shown important implications and capabili-ties of viscosity in describing inflationary era and late time acceleration of the universe; see also Ref.…”
Section: Introductionmentioning
confidence: 99%
“…A similar work has been done in reference [39], however, in constraining the parameters (ζ 0 , ζ 1 , ζ 2 ), the authors fixed either ζ 1 or ζ 2 as zero while evaluating the other. In a later work [40] we found that a general evolution of the universe with all the conventional phases (radiation epoch, matter dominated epoch and later acceleration) can be described without any causality violation only when the bulk viscous coefficient is a constant, ζ = ζ 0 .…”
Section: Introductionmentioning
confidence: 88%
“…The coefficient ζ is basically a transport coefficient, hence it would depend on the dynamics of the cosmic fluid. We consider the most general form for the bulk viscous coefficient ζ, which is a linear combination of the three terms [38,39,40,55,56],…”
Section: Bulk Viscous Flrw Universementioning
confidence: 99%
See 2 more Smart Citations